The Efficacy of Moral Education and the Concept of the "Circle of Trust" in Reinforcing the Digital and Intellectual Security of the Child: An Analytical Study of the "Roblox" Environment and Interactive Platforms (The International Journal of Educational Sciences and Arts, 2026)
This study analyzed the effectiveness of moral education and the concept of the "Circle of Trust" in enhancing the digital and intellectual security of children, using the Roblox platform and interactive platforms as a model. The research problem stemmed from the gap resulting from accelerated digital transformation and the emergence of novel intellectual and behavioral threats (such as grooming, social engineering, and dark patterns) that bypass traditional control mechanisms, exploiting the characteristics of User-Generated Content (UGC). The study adopted an integrated descriptive-analytical approach combined with direct scientific observation and content analysis tools, in addition to the inductive method to track and analyze three documented real-world cases. The study reached pivotal results, most notably: the failure of automated algorithmic monitoring systems to detect coded language and ideological symbols, and the existence of a close correlation between the success of digital grooming and the collapse of the "Secure Base" within the family. The study concluded that the child's self-cognitive and moral immunization takes precedence over forced prohibition policies, and it presented a proposed preventive intervention matrix (Circle of Trust) graduated across three levels: Self, Family, and Trusted Digital Community.
Keywords: Effectiveness of Moral Education; Circle of Trust; Child’s Digital Intellectual Security; Roblox Environment; Interactive Platforms; User-Generated Content (UGC)